Distribution of organic matter, phytopigments and heterotrophic bacteria along the salinity gradient in the estuaries of small rivers of the Tatar Strait basin - Ludmila A. Garetova; Svetlana I. Levshina; Natalia K. Fisher; Sergey E. Sirotsky; Vladimir P. Shesterkin (Известия ТИНРО, 2016)
Distribution of total organic matter and its dissolved and suspended forms was investigated in two small estuaries with different morphometric characteristics, as Muchke and Toki Lakes, in late July 2014 at the low tide phase. The time of survey was distinguished by low river discharge and high tides. Content of all forms of organic matter and hydrocarbons was higher in the estuarine waters, as compared with fresh river water, regardless of salinity. The dissolved form prevailed (79.7-98.6 % of the total organic matter content) with concentrations of 5.2-35.7 mg/l. Chlorophyll a dominated (up to 87 %) among phytopigments in both estuaries that corresponded to active development of microalgae. Toki Lake was distinguished by higher productivity and microplankton abundance. On the contrary, allochthonous organic matter was more abundant in Muchke Lake, where interrelation between destructors (heterotrophic bacteria number) and primary producers (Chl a concentration) was observed. Oil-oxidizing microorganisms were up to 60 % of the heterotrophic bacteria number. The hydrocarbons content exceeded the maximal permissible level: 3.6 and 4.5 MPL in Muchke and Toki Lakes, respectively. Both estuaries were subjected to chronic hydrocarbon pressure.